Breast cancer risk variants at 6q25 display different phenotype associations and regulate ESR1, RMND1 and CCDC170 - Dunning, Alison M; Michailidou, Kyriaki; Kuchenbaecker, Karoline B; Thompson, Deborah; French, Juliet D; Beesley, Jonathan; Healey, Catherine S; Kar, Siddhartha; Pooley, Karen A; Lopez-Knowles, Elena; Dicks, Ed; Barrowdale, Daniel; et al. (Nature genetics, 2016)
We analyzed 3,872 common genetic variants across the ESR1 locus (encoding estrogen receptor α) in 118,816 subjects from three international consortia. We found evidence for at least five independent causal variants, each associated with different phenotype sets, including estrogen receptor (ER(+) or ER(-)) and human ERBB2 (HER2(+) or HER2(-)) tumor subtypes, mammographic density and tumor grade. The best candidate causal variants for ER(-) tumors lie in four separate enhancer elements, and their risk alleles reduce expression of ESR1, RMND1 and CCDC170, whereas the risk alleles of the strongest candidates for the remaining independent causal variant disrupt a silencer element and putatively increase ESR1 and RMND1 expression.
Keywords: Polymorphism, Single Nucleotide; exprese genu; regulace genové exprese u nádorů; Humans; sekvence nukleotidů; Gene Expression; genetické asociační studie; Protein Binding; jednonukleotidový polymorfismus; Female; rizikové faktory; lidské chromozomy, pár 6; Phenotype; lidé; Cell Cycle Proteins; transportní proteiny; Carrier Proteins; Breast Neoplasms; ženské pohlaví; Base Sequence; Chromosomes, Human, Pair 6; Genetic Association Studies; fenotyp; Genetic Predisposition to Disease; genetická predispozice k nemoci; Estrogen Receptor alpha; vazba proteinů; proteiny buněčného cyklu; alfa receptor estrogenů; nádory prsu; Gene Expression Regulation, Neoplastic; Risk Factors